The Effect of Profitability, Liquidity and Solvability on Firm Value with Firm Size as Moderating Variable in Plantation Sector Company on The Indonesia Stock Exchange for The Period 2020 - 2024 - Situmorang, Renovand Mikael; Toni, Nagian; Ariesa, Yeni; Sitanggang, Tina Novianti; Aktar, Salim (Sekolah Tinggi Ilmu Ekonomi Sultan Agung, 2026)
This study aims to examine the influence of profitability, liquidity, and solvency on firm value with firm size as a moderating variable in plantation companies listed on the Indonesia Stock Exchange (IDX) during the period 2020–2024. Using a quantitative approach, this research employs the Structural Equation Modeling-Partial Least Squares (SEM-PLS) method to analyze the relationships among variables. The sample consists of 18 plantation companies selected using purposive sampling based on the availability and completeness of financial statements. The results reveal that profitability and liquidity have a positive and significant effect on firm value, while solvency does not significantly affect firm value. Additionally, firm size is found to moderate the relationship between profitability and firm value but does not moderate the effects of liquidity and solvency. These findings highlight the importance of profitability and liquidity management in enhancing firm value, particularly in the plantation sector. The study contributes to the understanding of financial determinants affecting firm value and provides practical insights for investors and corporate decision-makers.